2002
DOI: 10.1177/073953290202300206
|View full text |Cite
|
Sign up to set email alerts
|

Olympic Photo Coverage Fair to Female Athletes

Abstract: A content analysis of four Florida dailies and one national newspaper during the 2000 Games shows that newspaper editors included fair numbers of women in Olympic photos and chose photos that depicted female athletes in a realistic manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 0 publications
2
59
1
Order By: Relevance
“…In the same vein, the focus of reports on women's sports has been found to be placed on their appearance and private lives rather than the athletic aspect of the sport (Bissell & Duke, 2007;Hardin, Chance, Dodd, & Hardin, 2002;Jones, 2006). Finally, analyses of the Olympic games since 2000 have shown differences in how commentators analyze success or failure by gender.…”
Section: Olympic Coverage: Some Sociological Differencesmentioning
confidence: 95%
“…In the same vein, the focus of reports on women's sports has been found to be placed on their appearance and private lives rather than the athletic aspect of the sport (Bissell & Duke, 2007;Hardin, Chance, Dodd, & Hardin, 2002;Jones, 2006). Finally, analyses of the Olympic games since 2000 have shown differences in how commentators analyze success or failure by gender.…”
Section: Olympic Coverage: Some Sociological Differencesmentioning
confidence: 95%
“…Some recent research, however, indicates female athletes may receive more media coverage in international sporting competitions (Hardin et al, 2002;Jones & Greer, 2012). Still, many scholars argue the invisibility of female athletes in media coverage amounts to what Tuchman referred to as ''symbolic annihilation'' (e.g., Bishop, 2003).…”
Section: Sports Media and Gender Stereotypesmentioning
confidence: 96%
“…In 2000, Messner, Dunbar, and Hunt identified a consistent ''televised sports manhood formula'' in sports programming (including sports events, news programs, and commercials) that promoted and reinforced the hegemonic masculine ideals of male domination and female sexual objectification (p. 380). It is important to note, however, recent studies found men and women participating in international sporting events, such as snowboarding, were equally perceived with masculine and feminine characteristics (Hardin, Chance, Dodd, & Hardin, 2002;Jones & Greer, 2012). Yet, in most sports media men are typically the central focus (Messner et al, 2000;Sabo & Jansen, 1992).…”
Section: Introductionmentioning
confidence: 95%
“…Historically, the print media have perpetuated sexual difference by portraying female athletes as passive participants in sports considered feminine (Hardin, Chance, Dodd, & Hardin, 2002). The ABC and BBC continued this trend.…”
Section: Photographic Content-active and Passive Athletesmentioning
confidence: 99%